Social reconstruction of intergroup relations after conflict - Ajduković, Dean; Čorkalo Biruški, Dinka (2009)
Several concepts have been proposed to describe improvement in intergroup relations after a violent conflict: resolution, conflict transformation, co-existence and reconciliation. The concept of reconciliation has received increased attention in the recent years. It includes several critical components, such as: Honest acknowledgment of the harm/injury each party has inflicted on the other ; Sincere regrets and remorse for the injury done ; Readiness to apologize for one’ s role in inflicting the injury ; Readiness of the conflicting parties to ‘ let go’ of the anger and bitterness caused by the conflict and the injury ; Commitment by the offender not to repeat the injury ; Sincere effort to redress past grievances that caused the conflict and compensate the damage caused to the extent possible ; Entering into a new mutually enriching relationship (Assefa, 1999). However, the fact that most research on reconciliation has been done at the interpersonal level limits our knowledge about the intergroup reconciliation. Reconciliation implies profound transformation of the whole socio-psychological framework which is burdened by past wrongs and suffering, into a positive and collaborative, forgiving, trusting and mutually agreeable relationship by the majority of the adversary groups. Nadler (2002) proposed the concepts of instrumental and socioemotional reconciliation. Instrumental reconciliation involves a series of practical steps that contribute to intergroup rapprochement when the socioemotional conditions are not conductive to reconciliation. We propose that the concept of social reconstruction of intergroup relations provides a realistic description of the processes between former adversary groups, especially when they continue to live in the same community. We refer to the social reconstruction as a process within and around a community which brings its damaged social functioning to an improved level of interpersonal and groups relations and renews the community social fabric (Ajdukovic, 2004 ; 2005).
Projekt MZOS
ENG